IMPLEMENTATION OF A REPRODUCIBLE 5G STANDALONE TESTBED USING OPEN-SOURCE COMPONENTS (Journal of Problems in Computer Science and Information Technologies, 2025)
Deploying a 5G Standalone (SA) network is often constrained by cost, complexity, and limited access to RF hardware. This paper describes a practical, software-defined 5G SA implementation assembled entirely from open-source components Open5GS for the 5G Core, srsRAN for gNB and UE, MongoDB for subscriber data, and ZeroMQ for RF emulation to enable end-to-end connectivity without radios. The blueprint details service initialization order, subscriber provisioning, and configuration alignment across PLMN, TAC, DNN, and key material, followed by validation of UE registration, PDU session establishment, and user-plane data transfer. On the reference setup, the system achieves low round-trip latency (≈1.34 ms), high throughput (≈847 Mbps TCP downlink and ≈823 Mbps uplink), and rapid PDU session setup (≈0.22 s), supporting repeatable functional and performance testing in a laboratory environment. The described approach lowers the barrier to 5G experimentation for teaching, prototyping, and research while providing a reproducible path from basic bring-up to performance evaluation. Limitations include the use of emulated RF and a single-cell scenario; nevertheless, the workflow can be extended to over-the-air SDR tests, mobility, and slicing when needed.